SEISMIC VELOCITY STRUCTURE OF CIANJUR 5.6 MW EARTHQUAKE SOURCE AREA BY USING ITB TEMPORARY SEISMOGRAPHIC NETWORK - Fikri Azhari, M.
On November 21, 2022, a destructive earthquake with a magnitude of 5.6 Mw and a depth of 10 km rocked Cianjur and the surrounding area. This earthquake was identified as a shallow crustal earthquake which was then followed by a series of aftershocks that have caused economic losses, building damage, and loss of life. The local fault that causes this earthquake is still being debated considering that the epicenter of the earthquake is quite far from the Cimandiri Fault and Gede Volcano, so further investigation is needed regarding the complexity of the characteristic of the earthquake using seismic tomography. Data acquisition was carried out by installing a seismograph network of 20 stations consisting of 1 type of broadband seismometer and 19 types of short-period seismometer. The stages of data processing included determining the arrival time of the P and S waves from the aftershocks for the period 22 November – 23 December 2022, determining the location of the hypocenter using the non-linear method, and tomographic inversion using the least-square method. A total of 514 events were obtained consisting of 4494 P-wave and 3379 S-wave arrival times recorded by 20 temporary seismograph networks. Analysis of aftershocks shows that the hypocenters are distributed at a depth of 3-10 km with the Northwest-Southeast trending cluster (NNW-SSE) with a segment length of 8-10 km. The tomograms show that most of the 5.6 Mw Cianjur aftershocks occurred in zones with high velocity and low vp/vs ratio. The anomaly is associated with increased dry crack density. In addition, it was found that some aftershock clusters were in the low-velocity zone and a high vp/vs ratio indicated fluid intrusion that filled the rock fracture in the earthquake source area. The resolution tests show that the tomogram can be interpreted up to 10 km in depth.